Application of Fractional Co2 Laser Modification of PEEK in Dental Implants, In vivo Study (Medico Legal Update, 2021)
This study aimed to Modify the PEEK surface using Fractional CO2 laser in different range of parametersto change the surface topography regarding roughness and wettability to enhance osseointegration. A PEEKblock (Ceramill PEEK 98X20 N -JUVORA dental innovations, UK) was used to prepare substrate. By CADCAM system, PEEK was cut into discs (2 mm thickness and 10 mm diameter). the discs were smoothed bysilicon carbide paper of 500 grit and a rotation motion, polishing machine at 200 rpm for one minute usedto polish the discs, finally cleaned with ethanol alcohol using ultrasonic cleaner. Different parameters weretested to study their effects on PEEK surface; therefore, several trails were done using Fractional CO2 laserdevice. Surfaces of the irradiated PEEK discs were examined microscopically at different magnificationpower. Then SEM was used. Then, PEEK samples were scanned by (EDS). Range of powers were used (2,4, 6, 8, 10, 12) W The distance between spots was 0.2mm and 0.2 ms pulse duration to ensure maximumcoverage of laser effect. The energy range was (4 - 25) which was n’t enough to produce any effect. To testthe effect of pulse duration different values were also studied starting from 0.2ms then increase the pulseduration. 0.4,0.6,0.8 ms to increase the energy per pulse accordingly. Starting from short pulse durationup to 0.6ms there was no effect even when the power increased. At 0.8 ms pulse duration, the effect wasrecognized on the specimen surface. The collected data of previous trials direct the operator to reduce pulseduration to have best criteria, including surface roughness, wettability, without carbonization or cracks.Conclusions: Successful modification of PEEK surface can be done with fractional CO2 laser. Laserparameters as power, pulse duration, distance between spotes and number of scans are key factors induceddifferent range of effect considering material’s properties.